2017
DOI: 10.1016/j.alit.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety, efficacy, pharmacokinetics and pharmacodynamics of omalizumab in children with severe uncontrolled asthma

Abstract: Long-term treatment with omalizumab is well-tolerated and effective in children with uncontrolled severe allergic asthma. No new safety findings were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
0
29
0
4
Order By: Relevance
“…In children <12 years old, only 5 cases were reported (with partial or complete remission in all), so the level of evidence of efficacy is very low. The safety profile is better known from extensive experience treating severe allergic asthma, and omalizumab is generally well tolerated in RCTs, although long‐term follow‐up data are not available . The main severe risk is anaphylaxis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children <12 years old, only 5 cases were reported (with partial or complete remission in all), so the level of evidence of efficacy is very low. The safety profile is better known from extensive experience treating severe allergic asthma, and omalizumab is generally well tolerated in RCTs, although long‐term follow‐up data are not available . The main severe risk is anaphylaxis .…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile is better known from extensive experience treating severe allergic asthma, and omalizumab is generally well tolerated in RCTs, although long-term follow-up data are not available. 25 The main severe risk is anaphylaxis. 26 Our review showed more data with cyclosporine (n = 18) than omalizumab (n = 5) in children.…”
Section: Treatmentsmentioning
confidence: 99%
“…Also, there is reason to suppose that antieosinophil strategies may be deleterious in children, given the role of the eosinophil in immune homeostasis [74]. There are extensive paediatric data on efficacy and safety of the anti-IgE monoclonal omalizumab [75][76][77], so there should be no reason not to replicate these studies for other anti-IL-5 strategies, in the absence of a reliable biomarker of efficacy. In summary, it is essential to perform paediatric trials of these new agents that evaluate the impact of these treatments on development and long-term outcomes, and also to pursue research into biomarkers of efficacy [78].…”
Section: Conditional Lowmentioning
confidence: 99%
“…In patients with severe allergic asthma, the add-on treatment with omalizumab has been shown to reduce the risk of exacerbations [113117], the asthma symptoms [113,114,116,118], and the use of OCS [118] and ICS [115], as well as to improve the quality of life and lung function [113,114,116], without significant safety concerns. These beneficial effects of omalizumab first shown in randomized clinical trials have been confirmed in longer term real-life studies [119121], and appear to be independent on patients’ comorbidities [118].…”
Section: Management Of Severe Asthmamentioning
confidence: 99%